Mechanical Performance of Cup-spherical-shaped and Straight Form Braided Esophageal Stent - Haixia Zhao; Ying Liu; Xiaoyu Ni; Fengming Xia; Xiao Zhang (Institute of Advanced Engineering and Science, 2013)
This article introduces the application background and research overview of esophageal stent. The finite element models of two different forms of braided esophageal stent, such as cup-spherical-shaped and straight shaped, are created. Based on the configuration of material model selection and boundary condition, the stress and axial elongation of the stent with different wire numbers, different wire diameters and different leads are compared. The analysis results show that the maximum stress increases with the increase of the wire diameter and head, but decreases with the increase of the lead in straight stent while the maximal stress has a positive relationship with the wire diameter in cup-spherical-shaped stent. In the case the other parameters are the same, it is shown that the cup-spherical-shaped stent has the minimal stress when the crown number is 24. Meanwhile, the analysis results show that the lead has a great impact on the axial elongation of braided stent. In the case all parameters are the same, the axial elongation of cup-spherical-shaped stent is less than that of straight stent, which conclusively proves that the performance of cup-spherical-shaped stent is superior to that of the straight stent. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3512